Effects of particle morphology of ZnO buffer layer on the performance of organic solar cell devices - Mbule, P. S.; Kim, T. H.; Kim, B. S.; Swart, H. C.; Ntwaeaborwa, O. M. (ELSEVIER SCIENCE BV, 2013)
The performance of poly(3-hexyltheopene):[6,6]-phenyl C61-butyric acid methyl ester or P3HT:PCBM based organic solar cell (OSC) devices can be improved by adding an electron extraction layer of a wide band gap semiconducting material such as ZnO or TiO2 that facilitates the electron transport from the photo-active layer (P3HT:PCBM blend) to the top metal electrode (e.g. Al) and, at the same time, blocks holes from reaching the top electrode. Other factors that determine performance of the OSC devices include morphology, thickness and donor-acceptor ratio. In this study we investigated the effects of concentration and particle morphology (nanoparticle versus nanoflake) of ZnO electron extraction layer on the performance of the OSC devices with configuration ITO/PEDOT:PSS/P3HT:PCBM/ ZnO/Al. The concentration of ZnO nanoparticle or nanoflake solutions was varied from 0.5 to 20 mg/ml. A power conversion efficiency (PCE) of 3.08% was recorded from devices incorporating ZnO nanoflake electron extraction layer, whereas PCE of 2.37% was recorded from devices with ZnO nanoparticles as the electron extraction layer. The maximum PCE was obtained from a concentration of 0.5 mg/ml ZnO for both devices. The influence of the particle morphology and the concentration of the ZnO electron extraction layer on the general performance of the OSC devices is discussed in detail. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: TO-ROLL FABRICATION; POLY(3-HEXYLTHIOPHENE); PHOTOLUMINESCENCE